Effects of parenteral administration of enrofloxacin on electrocardiographic parameters in hospitalized dogs - Ramírez, Carlos Fernando Agudelo; Scheer, Peter; Tomenendálová, Jaroslava (Acta veterinaria Brno, 2012)
The effect of enrofloxacin on the QT interval of the electrocardiogram was studied in 30 hospitalized dogs. The experimental group (n = 15) received enrofloxacin parenterally (subcutaneously) at a dose of 5 mg/kg twice daily and amoxicillin-clavulanate intravenously at a dose of 22 mg/kg three times daily. The control group (n = 15) received only amoxicillin-clavulanate. Electrocardiography was carried out for 5 min once daily for 6 days. The QT interval was corrected by four different formulae. No differences were found between the two groups or within each group for the duration of the study. On the last day of the study the average QT interval for the control and experimental groups was 213.2 ms and 202.9 ms, respectively. Enrofloxacin did not cause prolongation of the QT or corrected QT intervals. We can conclude that the parenteral administration of enrofloxacin in non-cardiac dogs does not adversely affect the electrocardiographic indicators (no prolongation of the QT or corrected QT interval) and does not induce ventricular arrhythmias. Parenteral use of enrofloxacin is thus safe and effective in non-cardiac dogs.
Keywords: Cardiac Electrophysiology; repolarizace; injekce; Injections; Dogs; srdeční elektrofyziologie; zvířata; psi; bakteriální infekce; Fluoroquinolones; mužské pohlaví; Electrocardiography; QT interval; elektrokardiografie; Bacterial Infections; enrofloxacin; ženské pohlaví; fluorochinolony; Animals; Male; Enrofloxacin; Female